A diverse ant fauna from the mid-cretaceous of Myanmar (Hymenoptera: Formicidae). - Phillip Barden; David Grimaldi (PLoS ONE)
A new collection of 24 wingless ant specimens from mid-Cretaceous Burmese amber (Albian-Cenomanian, 99 Ma) comprises nine new species belonging to the genus Sphecomyrmodes Engel and Grimaldi. Described taxa vary considerably with regard to total size, head and body proportion, cuticular sculpturing, and petiole structure while all species are unified by a distinct shared character. The assemblage represents the largest known diversification of closely related Cretaceous ants with respect to species number. These stem-group ants exhibit some characteristics previously known only from their extant counterparts along with presumed plesiomorphic morphology. Consequently, their morphology may inform hypotheses relating to basal relationships and general patterns of ant evolution. These and other uncovered Cretaceous species indicate that stem-group ants are not simply wasp-like, transitional formicids, but rather a group of considerable adaptive diversity, exhibiting innovations analogous to what crown-group ants would echo 100 million years later.